Implementation of Shoe MSME Empowerment Policy as an Effort to Improve Competitiveness and the Local Economy of Mojokerto City - Azizatul Kamaliyah Suwandi; Ika Devy Pramudiana; Sapto Pramono (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze how the government policy of Mojokerto City is implemented to support the empowerment of shoe SMEs and to identify the factors influencing the success or failure of the policy. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. Data was collected from shoe SMEs, relevant government officials, and supporting institutions. Data analysis was conducted using Edwards III's public policy implementation theory, which includes four indicators: communication, bureaucratic structure, resources, and implementer disposition. The findings of this study show that although the policy for empowering shoe SMEs has had a positive impact in several areas, such as improving product quality and marketing awareness, there are still barriers in terms of inter-institutional coordination, access to funding, and human resource quality. The conclusion of this study is that the implementation of the shoe SME empowerment policy in Mojokerto City can succeed with improvements in more effective communication, better coordination between institutions, and strengthening the resources needed by SMEs. Recommendations for the local government include simplifying administrative procedures, increasing access to funding, and enhancing entrepreneurship training relevant to the needs of shoe SMEs. Therefore, this policy is expected to have a greater impact on competitiveness and the local economy.